2013
DOI: 10.1068/c11319
|View full text |Cite
|
Sign up to set email alerts
|

Social Enterprise and Ethnic Minorities: Exploring the Consequences of the Evolving British Policy Agenda

Abstract: Recent year have seen successive British governments move social enterprise centre stage as a policy construct. Yet there remains little understanding as to whether this policy direction provides new opportunities for engagement for migrant and ethnic minority groups or acts to reinforce past processes of exclusion. This article addresses this issue by examining the nature and extent of migrant and ethnic minorities' involvement in social enterprise activity and the resulting implications for policy and practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Within the UK, the experiences of Black and ethnic minority academics is gaining attention. Black and ethnic minority, within the UK, refers to those whose cultural heritage differs from that of the dominant group and may include first and second generation migrants, refugees and asylum seekers (Sepulveda, Syrett, & Calvo, 2013), Ahmed (2009) has identified that black feminist academic women, by their very presence, disturb the Academy, including white feminism in the Academy by revealing its racism and colonialism. The marketisation of higher education has been identified as one of the 'forms of regulation of Black feminism' within the Academy, whereby Black feminism is forced to operate within a market-driven system which defines 'value' (Ali, Mirza, Phoenix, & Ringrose, 2010, p. 648).…”
Section: Feminist Academicsmentioning
confidence: 98%
“…Within the UK, the experiences of Black and ethnic minority academics is gaining attention. Black and ethnic minority, within the UK, refers to those whose cultural heritage differs from that of the dominant group and may include first and second generation migrants, refugees and asylum seekers (Sepulveda, Syrett, & Calvo, 2013), Ahmed (2009) has identified that black feminist academic women, by their very presence, disturb the Academy, including white feminism in the Academy by revealing its racism and colonialism. The marketisation of higher education has been identified as one of the 'forms of regulation of Black feminism' within the Academy, whereby Black feminism is forced to operate within a market-driven system which defines 'value' (Ali, Mirza, Phoenix, & Ringrose, 2010, p. 648).…”
Section: Feminist Academicsmentioning
confidence: 98%
“…Much of the early writing on SEs was atheoretical and searching for the positive (Parkinson and Howorth ; Sepulveda et al . ) and, in response, more recent research has advanced new theories to explain their emergence (Tracey et al . ), management (Battilana and Dorado ; Pache and Santos ) and, more critically, the ethics, power and emancipatory aspects of SE (Teasdale ).…”
Section: Introductionmentioning
confidence: 99%
“…Social enterprise was presented as offering a way forward (notably, to reduce grant dependency among charities) through its ‘business like’ model that is more suitable for charities than the ‘for‐private‐profit’ model in terms of organizations' (social) mission and values, (democratic) governance and (social) ownership (Sepulveda et al . ).…”
Section: From Social Enterprise Idea To Policy and Practice: The Casementioning
confidence: 97%